A multicenter study investigating the genetic analysis of childhood steroid-resistant nephrotic syndrome: Variants in COL4A5 may not be coincidental. - Sheng Li; Miaoyue Hu; Chao He; Yu Sun; Weifang Huang; Fengying Lei; Yunguang Liu; Zengpo Huang; Yongqiu Meng; Wenjing Liu; Xianqiang Lei; Yanfang Dong; et al. (PLoS ONE)
This study aimed to discuss the pathogenic hereditary factors of children with steroid-resistant nephrotic syndrome (SRNS) in Guangxi, China. We recruited 89 patients with SRNS or infantile NS from five major pediatric nephrology centers in Guangxi, and conducted a retrospective analysis of clinical data. Whole-exome sequencing analysis was also performed on all patients. The risk of progression to chronic kidney disease (CKD) was assessed using the Kaplan-Meier method and Cox proportional hazards model. The study included 69 male and 20 female participants from 86 distinct families, with the median age of disease onset being 48 months (interquartile range: 24-93). Overall, 24.7% had a family history of SRNS, whereas 13.5% exhibited extra-kidney manifestations. We identified disease-causing variants in 24.7% (22/89) of patients across eight screened genes. The most frequently detected variant was found in COL4A5, followed by NPHS2 (5.6%), NPHS1 (2.2%), PAX2 (2.2%), WT1 (1.1%), LMX1B (1.1%), NUP105 (1.1%), and COL4A6 (1.1%). Twelve of the 26 pathogenic variants were determined to be de novo. Based on gene detection results, pathogenic variants were categorized into two groups: identified and unidentified variants. The identified variant group demonstrated a significant association with positive family history, steroid resistant-style, and response to immune therapy (P<0.001). Patients with the identified genetic variant were approximately ten times more likely to develop CKD (P<0.001) than those in the unidentified group at the last follow-up. Kidney biopsy was performed on 66 patients, and minimal change disease was the most prevalent histopathological diagnosis (29 cases; 32.6%). These findings suggest that children diagnosed with SRNS exhibit a diverse range of genetic alterations. We identified the COL4A5 variant as the predominant genetic abnormality and a low frequency of NPHS1 gene involvement in these children. Gene variants may serve as an independent predictor for SRNS progression to CKD.